Depression increased risk of coronary heart disease: A meta-analysis of prospective cohort studies - Cao, Hongfu; Zhao, Hui; Shen, Li (Frontiers in Cardiovascular Medicine, 2022)
Background: Depression, as an independent risk factor, can lead to a substantially increased risk of coronary heart disease (CHD). The overall body of evidence involving depression and CHD is not consistent. Therefore, we performed an update meta-analysis to evaluate the association between depression and the risk of patients with CHD. Methods: Studies were identified through a comprehensive literature search of the PubMed, Embase, and the Cochrane Library database from its inception to September 28, 2021 for titles/abstracts with restricted to English language articles. The literature was screened according to the inclusion and exclusion criteria. Along with data extraction, we evaluated the quality of eligible studies using the Newcastle- Ottawa Scale (NOS). The primary outcome was fatal or non-fatal CHD. We calculated relative risk with 95% confidence intervals using a random- effects models. The protocol was registered in the PROSPERO registration (registration number CRD42021271259). Results: From 9,151 records, we included 26 prospective cohort studies published from 1998 to 2018, consisting of 402,597 patients. Either in depression-exposured group or nondepression-exposured group, the mean age of all participants ranged from 18 to 99 years. Moreover, the NOS scores of these studies are eventually indicated that the quality of these eligible studies was reliable. In general, the pooled results showed that patients with depression had a higher risk of CHD compared to patients without depression (relative risk (RR) =1.21, 95% confidence interval (CI):1.14 to 1.29). Additionally, the funnel plot appeared to be asymmetry, indicating there existing publication bias for the pooled results between depression and CHD. A sensitivity analysis was used to assess the stability of the relationship between depression and CHD that indicating the results robust (RR=1.15,95%CI:1.09 to 1.21). Conclusions: Depression may increase risk of CHD. Future studies on the share pathogenic mechanisms of both depression and CHD may develop novel therapies.